CONSTRUCTING ECOLOGICAL MEANING IN CORPORATE SUSTAINABILITY REPORTING: A CRITICAL ECOLINGUISTICS ANALYSIS OF SINAR MAS LAND - Muhammad Munawir; Junaidi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study analyses the use of ecological meanings in Sinarmas Land's Sustainability Reports (2017–2024), a prominent Indonesian homebuilder. The study employs Arran Stibbe's